Housing environments and older women theoretical perspectives - Datlen, Barbara M. (Department of Humanities, Nova Scotia Agricultural College, 1995)
As the Canadian population ages it is becoming more widely recognized that the quality of housing environments for the elderly are of much importance in enhancing their overall quality of life. Furthermore, professionals in the planning field are becoming aware of the significance of the nieghbourhood to the elderly in their daily lives. Social gerontologists, community planners, housing professionals and social service workers are now playing more attention to questions regarding nieghbourhood and housing environments, particularly as the proportion of the very-old population (75 years of age and over) increases and the trend away from institutionalization similarly increases.